Electronics and microprocessor technology - Boliukh, Volodymyr; Markov, Vladyslav; Honcharov, Yevgen; Poliakov, Ihor; Kriukova, Natalia; Kashansky, Yuriy (Національний технічний університет "Харківський політехнічний інститут", 2024)
The course of five laboratory works from the section "Electronics and microprocessor technology" of the discipline "Electrical engineering, electronics and microprocessor technology" has been presented in the form of a complex independent work for preparation for the execution of these laboratory works. Theoretical material on the design and principle of operation of devices, as well as the methodology for their calculation, are provided. The laboratory manual has been intended for independent work of students in the preparation and execution of laboratory, calculation and graphic works, preparation for tests and exams. Part I was published in 2022, Part II was published in 2023.
Keywords: laboratory manual; electrical engineering; electronics; microprocessor technology; electrical engineering; laboratory works